Relationship between brain size and digestive tract length support the expensive-tissue hypothesis in Feirana quadranus - Fu, Yiping; Song, Yanling; Yang, Chao; Liu, Xinyi; Liu, Yenan; Huang, Yan (Frontiers in Ecology and Evolution, 2022)
The brain is among the most energetically costly organs in the vertebrate body, while the size of the brain varies within species. The expensive-tissue hypothesis (ETH) predicts that increasing the size of another costly organ, such as the gut, should compensate for the cost of a small brain. Here, the ETH was tested by analyzing the relationship between brain size variation and digestive tract length in a Swelled-vented frog (Feirana quadranus). A total of 125 individuals across 10 populations ranging from 586 to 1,702 m a.s.l. from the Qinling-Daba Mountains were sampled. With the increase in altitude, the brain size decreases and the digestive tract length increases. Different brain regions do not change their relative size in a consistent manner. The sizes of telencephalon and cerebellum decrease with the increase in altitude, while the olfactory nerve increases its size at high altitudes. However, the olfactory bulb and optic tectum have no significant relationship with altitude. After controlling for snout-vent length (SVL), a significant negative correlation could be found between brain size and digestive tract length in F. quadranus. Therefore, the intraspecific variation of brain size follows the general patterns of ETH in this species. The results suggest that annual mean temperature and annual precipitation are environmental factors influencing the adaptive evolution of brain size and digestive tract length. This study also suggests that food composition, activity times, and habitat complexity are the potential reasons driving the adaptive evolution of brain size and digestive tract length.